A matter of justice ebook - Todd, Charles (Inspector Ian Rutledge Mystery,, 2009)
"Charles Todd hasn't made a misstep yet in his elegant series featuring Scotland Yard detective Ian Rutledge, and A Matter of Justice keeps the streak going." —Cleveland Plain Dealer The Washington Post calls the Ian Rutledge novels by Charles Todd, "one of the best historical series being written today." A Matter of Justice—the eleventh in the New York Times Notable, Edgar® Award-nominated, and Barry Award-winning series—brings back the haunted British police inspector and still shell-shocked World War One veteran in a tale of unspeakable murder in a small English village filled to bursting with dark secrets and worthy suspects. A New York Times bestseller as spellbinding and evocative as the best of Ruth Rendell, Anne Perry, Martha Grimes, and P.D. James, A Matter of Justice represents a new high for this exceptional storyteller.